Assessment Supporting the Use of Outcropping Rock Evolutionary Intensity Measures for Prediction of Liquefaction Consequences. Issue 4 (November 2019) - Bullock, Zach; Dashti, Shideh; Liel, Abbie B.; Porter, Keith A.; Karimi, Zana
This study evaluates a variety of intensity measures (IMs) for predicting the liquefaction-induced residual settlement and tilt of shallow-founded structures. We use data from both numerical and physical (centrifuge) models of soil-foundation-structure systems. The relative quality of these IMs is quantified in terms of efficiency, sufficiency, and predictability. We consider both scalar and vector-valued IMs and evaluate the relative performance of IMs recorded at different locations (outcropping rock, within rock, far-field, and foundation) from nonlinear and equivalent-linear simulations. Cumulative absolute velocity (CAV) at outcropping rock is the optimum IM for predicting foundation settlement, while either outcropping rock CAV, peak ground velocity, or peak incremental ground velocity is optimum for predicting permanent foundation tilt. Vector IMs offer improvements to efficiency and sufficiency but may be impractical to predict.